The first clinical case of implantation of a composite frame xenopericardial bioprosthesis “MedEng-Bio” in the mitral position - B. N. Kozlov; K. A. Petlin; A. S. Pryakhin; A. V. Schedrin; D. S. Panflov; V. M. Shipulin (Бюллетень сибирской медицины, 2018)
The article presents the first clinical case of the implantation of a composite frame xenopericardial bioprosthesis “MedEng-Bio” in the mitral position. The special design of the prosthesis implantation procedure simplifies and reduces the risks associated with possible repeated operations.